Movements and habitat use of the night parrot Pezoporus occidentalis in south‐western Queensland. (1st July 2017) - Murphy, Stephen A.; Silcock, Jennifer; Murphy, Rachel; Reid, Julian; Austin, Jeremy J.
Abstract: The nocturnal, cryptic and geographically remote nature of night parrots, combined with their apparent rapid decline, means that very little is known of their biology or ecology. The discovery of a resident population in south‐western Queensland in 2013 provides the first opportunity to undertake detailed studies on this most enigmatic of birds. We attached a radio tag to a bird for 20 days in April 2015 and a GPS tag to another bird for 5 days in May 2016 to study movement patterns and habitat use. Both birds displayed similar behaviour but the GPS‐tagging provided a much finer resolution of spatial data. They called at dusk from their diurnal roosts amongst spinifex hummocks and then flew to more floristically diverse habitats dominated by large‐seeded species to feed. We conducted floristic surveys to describe the feeding grounds of the GPS‐tagged bird and make dietary inferences. This individual spent most of its time in highly diverse but ephemeral habitats, including seasonally inundated plains and depressions associated with the outer Diamantina floodplain and gilgais on ironstone plains. Prolifically seeding ephemeral species, most notably the annual grass Uranthoecium truncatum, dominate these feeding grounds. This work suggests that the habitat mosaic containing roost sites in close proximity to feeding grounds with key seed‐producing species is an important factor, rather than an association with spinifex or samphire alone. Further work is needed to examine movement patterns and habitat use in more typical dry seasons and the impact of cattle grazing on night parrot feeding areas, particularly with regard to seed production. The information presented here is vital for both in situ conservation of the Pullen‐Pullen‐Mt Windsor‐Diamantina population and for setting future research and survey priorities.